Tropical forests : regional paths of destruction and regeneration in the late twentieth century - Rudel, Thomas K. (Columbia University Press, 2005)
In Tropical Forests, Rudel analyzes hundreds of local studies from the past twenty years to develop a much-needed, global perspective on deforestation. With separate chapters on individual regions, including South and Central America, the Caribbean, and Africa, Rudel's work offers an up-to-date assessment of the world's tropical forests. In the concluding chapter, Rudel considers the implications of these trends and describes policy directions for conserving biodiversity and promoting sustainable development in each region.